TAJIKISTAN’S FOREIGN TRADE WITH NEIGHBORING COUNTRIES: NEW TRENDS AND SOCIAL AND POLITICAL IMPACTS - RYAZANTSEV, Sergey; PISMENNAYA, Elena; PICHKOV, Oleg; GARIBOVA, Farzona (CENTRAL ASIA AND THE CAUCASUS, 2019)
Tajikistan is a very isolated country with difficult access and limited transport connections to other countries in the region and beyond. Under such restricted conditions, international relations that enable economic development and promote social progress are crucial for Tajikistan. Considering the country’s geographic location, Tajikistan’s interaction with neighboring countries plays a major role in its international relations.The paper analyzes the foreign trade relations between Tajikistan and its neighboring countries—Afghanistan, China, Kyrgyzstan, and Uzbekistan. Examining Tajikistan’s border trade with these countries is relevant because it reflects the importance of this aspect’s influence on the country’s socio-economic development.Border trade, defined as the flow of goods and services over international land borders within a 30-kilometer range, plays an important role in supporting the livelihood of the population in the border areas. This trade is a pillar of the republic’s welfare. Moreover, by strengthening trade connections and promoting mutual understanding between different communities, border trade stimulates the maintenance of friendly relations between neighbors.